Interplay of motivation and self-regulation throughout the development of elite athletes - Jordalen, G.; Lemyre, P.-N.; Durand-Bush, N. (Qualitative Research in Sport, Exercise and Health, 2020)
Recent development in the understanding of human motivation has highlighted the crucial and reciprocal role of motivation on cognitive processes. In elite sport settings, athletes are subject to external forces that do not necessarily correspond with their inherent drives. However, they seem to develop cognitive competencies to cope with external forces, when planning, monitoring, and reflecting on their high-level achievements. The current study aims to explore likely interactions between motivation and cognitive processes as athletes develop from novice to elite levels. Five female Olympic and World Championship medallists were interviewed. A thematic analysis revealed how motivation and self-regulation competencies interchangeably influenced athletes` career trajectories asynchronously. Chronologically, four themes emerged: 1) Motivational shifts evoked planning and self-control competencies, 2) The external control constrained athletes` self-regulation, 3) Self-control and reflection in extrinsically driven athletes, and 4) Elite athletes` multidimensional motivation and self-regulation profile. Initially, intrinsic motivation prompted athletes` participation, but the competitive nature of sport activities led to a shift toward more external forms of motivation. This motivational shift was accompanied by changes in self-regulation competencies, particularly planning and self-control, rather than self-reflection. Over time, athletes` increased sport-specific self-confidence contributed to further refinement of self-regulation competencies and integrated motivational regulations. Rather than exploring motivation and cognitive competencies individually, current study findings highlight dynamic interactions between these concepts that influences athletes` ongoing development to elite level performances.